Levels of Dopamine and Beta-Endorphin Hormones in Iraqi Children with Autism Spectrum Disorder - Hasan, Hayder Atta Abdul-Jabbar; Maleek, Muthana Ibrahim (American Journal of Biology and Natural Sciences, 2025)
Autism is a neurodevelopmental disease that expresses itself in a variety of ways, most often within the first 3 years of a person's life. Difficulties in social communication and repetitive and stereotypical behaviors characterize it. The global prevalence of autism is estimated to be about 1 in 100 children, reaching up to 1 in 36 children in some high-income countries. This research focuses on studying the hormonal changes in children with Autism Spectrum Disorder (ASD) to improve scientific understanding of the biological changes associated with the disease. This study was conducted in Al-Zahra Teaching Hospital in Al-Kut / Iraq, on a sample of 50 children with autism (40 males and 10 females) aged 3 to 12 and a control group of 25 healthy children. Blood samples were collected from all participants. Dopamine and Beta-Endorphin were measured by using the ELISA technique. The mean dopamine level was significantly lower at a significance level of P≤0.05 in autistic children, 26.49 ng/L, compared to healthy controls, 44.5 ng/L. Conversely, beta-endorphin levels exhibited no statistically significant variations between the two groups, 22.85 pg/ml in autistic children and 21.1 pg/ml in healthy controls.